H Syndrome retrospectively diagnosed: The importance of recognizing cutaneous signs - Parodi, Aurora (Clin Case Rep, 2020)
We present a case of a retrospectively diagnosed H syndrome in a man who died of a probable heart infarction. We highlight the importance of recognizing cutaneous hallmarks of this syndrome for better clinical management and prevention.